Electronic Data Processing in Accounting Education. - Hein, Leonard; Mattessich, Richard; McCullough, Elzy V.; Seiler, Robert E.; Jones, Gardner (The Accounting Review, 1965)
Abstract The article focuses on recommendations made by the 1964 American Accounting Association Committee on Courses and Curricula–Electronic Data Processing. The committee recommended that at the undergraduate level, accounting students should be exposed to electronic data processing in stages. Added emphasis should be placed in the accounting systems course on logical information flows and on multi-dimensional information requirements rather than on the form and content of specific accounting records. At the master's degree level, the student must have at least the same proficiency as an undergraduate, but hopefully it will be at a more sophisticated level. At the doctoral level, accounting systems instruction is a distinct subject-matter area, as are accounting theory, internal accounting, taxes and auditing. A doctoral degree presumes at least a sound foundation knowledge in each of the broad accounting areas, with a high degree of expertise in the candidate's specialist area. The committee also recommended that substantial attention should be given both by individual schools and by the American Accounting Association, to the need for a re-orientation of accounting toward an analytical approach rather than one which is mainly descriptive.